Techno-economic assessment of pressure swing adsorption tail gas decarbonisation for blue hydrogen production - Golmakani, Ayub; Khallaghi, Navid; Amiri, Amirpiran; Manovic, Vasilije; Nabavi, Seyed Ali (Elsevier, 2025)
Steam methane reforming (SMR) is a leading technology for hydrogen production. However, this technology is still carbon-intensive since, in current SMR units, the PSA tail gas containing H2, CO, and CH4 is burned at the reformer with air and exits the stack at a CO2 purity of less than 5%, which is not feasible to capture. In this paper, we aim to either harness the energy content of this gas to generate power in a solid oxide fuel cell (SOFC) or burn it via chemical looping combustion (CLC) or oxy-combustion process to produce off-gas with high CO2 purity ready to storage. Therefore, an industrial-scale PSA with 72,000 Nm3/h feed capacity was modelled to obtain the tail gas flow rate and composition. Then, CLC, SOFC, and oxy-combustion were modelled to use tail gas. Finally, a techno-economic analysis was conducted to calculate each technology's levelised cost of hydrogen (LCOH). It was observed that CO2 purity for CLC meets the criteria for storage (>95%) without further purification. On the other hand, from the economic point of view, all three technologies show a promising performance with an LCOH of 1.9 €/kg.
Keywords: 4004 Chemical Engineering; 40 Engineering; 7 Affordable and Clean Energy; 13 Climate Action; Blue hydrogen; PSA tail gas; SOFC; CLC; Oxy-combustion